"Hide a Fact Rather than State it": The Holocaust, the 1940s Human Rights Surge, and the Cosmopolitan Imperative of International Law. Issue 1 (2nd January 2021) - Kurz, Nathan A.
ABSTRACT: Historians and legal scholars have used United Nations summary records for decades with little regard for the unsettled nature of these sources. This article grapples with a particular empirical finding with profound implications beyond the specific case under consideration: UN précis-writers systematically removed references to the Holocaust made by Jewish lobbyists from drafting documents associated with the 1948 Universal Declaration of Human Rights and the 1948 Genocide Convention. It reviews the political and bureaucratic logic that governed these excisions and examines the UN's process of document creation to illustrate how international legal epistemology stands in stark contrast to processes of historicization favoured by historians. Ultimately, this piece argues that scholars who use summary records of international legal proceedings need to be highly attuned to the ways in which international law's "cosmopolitan imperative" distorts primary sources.